2021
DOI: 10.1101/2021.02.24.432612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A synaptic novelty signal to switch hippocampal attractor networks from generalization to discrimination

Abstract: Episodic memory formation and recall are complementary processes that put conflicting requirements on neuronal computations in the hippocampus. How this challenge is resolved in hippocampal circuits is unclear. To address this question, we obtained in vivo whole-cell patch-clamp recordings from dentate gyrus granule cells in head-fixed mice navigating in familiar and novel virtual environments. We find that granule cells consistently show a small transient depolarization of their membrane potential upon transi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…(Guo et al, 2018), we propose a testable model for how our manipulation increases synchronous activity of principal neurons in CA1 and ACC. We predict that increasing granule cell recruitment of perisomatic inhibition onto CA3 neurons imposes sparseness and facilitates coordinated spiking or burst firing of CA3 neurons thus reducing the likelihood of recruitment of the same CA3 neurons to distinct ensembles (Csicsvari et al, 2000;de la Prida et al, 2006;Gómez-Ocádiz et al, 2021;Mori et al, 2007;Neubrandt et al, 2017;Sasaki et al, 2018;Torborg et al, 2010). In turn, assemblies of CA3 neurons encoding different contexts entrain activity of downstream ensembles of CA1 principal neurons.…”
Section: Discussionmentioning
confidence: 95%
“…(Guo et al, 2018), we propose a testable model for how our manipulation increases synchronous activity of principal neurons in CA1 and ACC. We predict that increasing granule cell recruitment of perisomatic inhibition onto CA3 neurons imposes sparseness and facilitates coordinated spiking or burst firing of CA3 neurons thus reducing the likelihood of recruitment of the same CA3 neurons to distinct ensembles (Csicsvari et al, 2000;de la Prida et al, 2006;Gómez-Ocádiz et al, 2021;Mori et al, 2007;Neubrandt et al, 2017;Sasaki et al, 2018;Torborg et al, 2010). In turn, assemblies of CA3 neurons encoding different contexts entrain activity of downstream ensembles of CA1 principal neurons.…”
Section: Discussionmentioning
confidence: 95%
“…How does PV mediated perisomatic inhibition of CA3/CA2 contribute to social recognition? Perisomatic inhibition of CA3/CA2 neurons may impose a sparse activity regimen that supports generation of distinct neuronal ensembles in response to an experience (Csicsvari et al, 2000; de la Prida et al, 2006; Gómez-Ocádiz et al, 2021; Guo et al, 2018; Mori et al, 2007; Neubrandt et al, 2017; Sasaki et al, 2018; Torborg et al, 2010; Twarkowski et al, 2022). Consistent with this idea, DGC recruitment of FFI in CA3/CA2 is randomly wired so as to provide blanket inhibition and govern network excitability in CA3 and CA2, rather than couple individual DGC-dependent excitation with inhibition onto distinct populations of pyramidal neurons (Neubrandt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that increasing FFI in DG ‒ CA3 decreases overlap between two context-associated ensembles in CA3 ( Guo et al, 2018 ). We predict that increasing granule cell recruitment of perisomatic inhibition onto CA3 neurons imposes a sparser activity regimen from DG to CA3 thereby reducing the likelihood of recruitment of the same CA3 neurons to distinct ensembles during learning ( Csicsvari et al, 2000 ; de la Prida et al, 2006 ; Gómez-Ocádiz et al, 2021 ; Mori et al, 2007 ; Neubrandt et al, 2017 ; Sasaki et al, 2018 ; Torborg et al, 2010 ). In turn, assemblies of CA3 neurons encoding different contexts entrain activity of downstream ensembles of CA1 principal neurons ( Choi et al, 2018 ; Csicsvari et al, 2000 ; de la Prida et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%